THE ROLE OF JOB SATISFACTION AND ADAPTIVE SELLING BEHAVIORS ON SALESPERSON’S PERFORMANCE - Mulyadi, Dedi; Khalida, Laras Ratu; Sinaga, Obsatar; Mohamad Yazid, Mohd Faizun (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this paper is to measure the relationship between job satisfaction and adaptive selling towards sales performance. Job satisfaction is one of the important variables used to measure the organization performance but this paper will have focused on the individual performance related to their sales activities. Adaptive selling is the method used in selling especially related to service based products. This paper focused on the life insurance industry where the sales of policy will depend on the individual subject to their requirements. The study was conducted using a sample of 158 insurance salespersons from five top cities in Indonesia. The results suggested that both job satisfaction and adaptive selling behaviors have significant relationship towards sales performance. The results indicate that both job satisfaction and adaptive selling is important towards sales performance. It means that organization need to focused more on the two variables. Sales related services may face fierce competition and sales agent is very important to support the success of the organization. Individual as agents need to play more role in selling and using the adaptive method in order to be more customer oriented. Organization at the same time must treat their employee in the best way to ensure and cultivate job satisfaction.